Oral health knowledge and practices: their influence on oral health status of auxiliary health workers in health centers of Mangalore, India - Mallikarjun Sajjanshetty; Ashwini Rao; Rajesh Gururaghavendran; Ramya Shenoy; B H Mithun Pai (Wolters Kluwer Medknow Publications, 2019)
Background: Disparity exists in the availability of dental care services in rural India as compared to urban setup. Majority of dental offices are set in urban areas, with little access to rural population, driving people to primary health centers for all health needs. In situations like these, auxiliary health workers can be delegated with the duties of oral health education to the masses provided they possess adequate information/knowledge regarding oral healthcare and practices. Aim: The aim of this study is to assess the influence of oral health knowledge (OHK) and oral health practices on the oral health status among auxiliary health workers in the health centers of Mangalore. Material and Methods: A cross-sectional study was carried out among the auxiliary health workers in Mangalore. OHK and practices were analyzed using a pretested, screening questionnaire. Oral health status was analyzed using the WHO Oral Health Assessment Form-1997. Data were analyzed using the Statistical Package for the Social Sciences software, version 16.0 (SPSS Inc., Chicago, IL, USA). Chi-square test and binary logistic regression test were employed. P < 0.05 was considered statistically significant. Results: Majority (72.8%) of the auxiliary workers had good OHK and followed recommended dental practices. Better OHK was associated with better oral health, namely lesser decayed teeth and more filled teeth (P < 0.05). Better OHK correlated negatively with missing teeth among participants (P < 0.05). Visiting a dentist in previous 6 months, brushing twice a day, and changing brush every 3 months were the important predictors of improved oral health (P < 0.05). Conclusion: Better OHK and practices can significantly impact the oral health status of auxiliary health workers in Mangalore. It also projects the impact that it can have on the oral health of rural population as auxiliary health workers are the first line of information for the underprivileged masses. Dedicated oral health programs to educate/train auxiliary workers in health centers can form an alternative approach to reach rural population.